Dye additives in vape liquids alarming - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Elil, Renganathan *; Long, Chiau Ming * (New Straits Times Press (M) Bhd., 2023)
Electronic cigarettes or vapes, including their liquids, are easily accessible in Malaysia due to inadequate regulation.